Manures and fertilizers - P.C. Das; P.C. Das (New Delhi Kalyani, 1993)
Manures and fertilizers are used to assist the growth of plant and these have the key role for assisting the fulfilment of green revolution of our contry.
Plant nutrients Micronutrients Manures Vermiculture Fertilizers
Keywords: Plant nutrients, Micronutrients, Manures